Hall currents and EDL effects on multiphase wavy flow of Carreau fluid in a microchannel having oscillating walls: A numerical study - Alqarni, M. M.; Riaz, Arshad; Firdous, Muazma; Lali, Ikram Ullah; El-Din, ElSayed M. Tag; Rahman, Shafiq ur (Frontiers in Physics, 2022)
In this analysis, the authors reveal the effects of electro-osmosis on the multiphase flow of Carreau fluid in a microchannel in the presence of Hall currents and solid particles. Moreover, the compliant channel walls are subject to oscillation occurring at the surface. To investigate the problem quantitatively, mathematical models for fluid phase and particulate phase have been structured. A lubrication approach is adopted due to laminar flow and the small dimensions of the channel. To produce the data, a system of differential equations is produced with the help of a numerical process performed on Mathematica through a built-in NDSolve tool. The results are presented graphically to examine the effects of various physical factors on the flow quantities. From pictorial discussion, it is gathered that the Helmholtz–Smoluchowski velocity parameter and the presence of an increasing amount of solid particles increasing the heat exchange while producing electro-kinetic energy. It is also found that velocity is a direct function of solid particles and compliant walls, but an inverse link is seen in the presence of electro-kinetic energy. Such studies can be employed with microfluidic devices and \may also be productive in medical and mechanical research.